Changes in tannin and pectic substances at different positions within a bunch of Cavendish Banana (Musa cavendishii L. var. Montel) during development and maturation - Mustaffa, Razali; Osman, Azizah; Mohamed, Suhaila; Yusof, Salmah (Universiti Putra Malaysia Press, 1997)
Studies were carried out on changes in the tannin content, alcohol insoluble solids (AIS) and pectin fractions (water, ammonium oxalate and sodium hydroxide solubles) of Cavendish banana variety Montel at different positions within a bunch during maturation and ripening. There was a significant decrease (P<0.01) in the tannin content between the different portions of hands within a bunch and between different fingers within a hand during maturity. AIS increased at the early stages, but it decreased significantly (P< O. 05) in the ripe fruits (week 12). There was a significant difference (P<0.05) in the pectic substances at different positions within a bunch during maturity. The pectins increased at the early stages, reaching a maximum at week 12 and then slowly decreased. At the end of maturation, the pectic substances started to increase slowly until ripening. There were also significant differences (P<0.05) in the tannin content, AIS and pectic substances during maturity between different portions of hands and fingers. However, significant differences (P<0.05) were observed between portions of hands within a bunch and between fingers within a hand during maturity stage; the top hands and upper fingers were higher in tannin, AIS and pectic substances contents than the middle and bottom hands within a bunch and lower fingers within a hand respectively.